CRIME SCENE INVESTIGATION, OBJECTS AND DOCUMENTS SAMPLING, SEARCH AND EVIDENCE COLLECTION DURING INVESTIGATION OF THE SMUGGLING OF MIGRANTS OFFENCE - Gina-Aurora NECULA (Legea și Viața)
The crime scene investigation, the examination of physical evidence - objects and documents -, as well as searches and evidence collection, are essential procedural actions for the evidence collection and administration of evidence in the investigation of the organizaed migrant smuggling. For this reason, this present study explores the specifics and particularities of these actions from a forensic perspective. The article is not limited only to theoretical aspects, but also integrates an extensive analysis of current judicial practice, relating it to the scientific foundations. The main objective of the scientific article was to examine the tactics applied in the conduct of these procedural actions, as well as to identify legislative gaps and inconsistencies in the application of judicial practice. Ultimately, the research aims to provide practical recommendations, based on a scientific approach, to support the prosecution authorities. The effective implementation of these recommendations would contribute to improving the process of investigating the organization of irregular migration, facilitating the work of prosecution authorities and strengthening the state’s obligations in the fight against crime.